Pendidikan Karakter Perspektif Al-Qur’an dan Hadis - Ansori, Muhammad Isa; Hudallah, Hudallah; Sholekah, Umma Rohmah (Lembaga Yasin AlSys, 2025)
Education is a fundamental aspect of human life, and in the Indonesian context, the urgency of character education continues to grow amid rising moral issues such as student brawls, drug abuse, and corruption. This study aims to examine the importance of character education in shaping students’ emotional and moral intelligence based on the principles of the Qur’an and Hadith. A literature study was conducted using a qualitative descriptive approach. The findings indicate that character education functions not only as the inculcation of moral values but also as a guide for navigating emotional and social challenges. The teachings of the Qur’an and Hadith emphasize values such as honesty, justice, and kindness, which serve as the foundation for the development of noble character. Ideally, character education should begin in early childhood, with active involvement from parents and teachers as behavioral role models through habituation, exemplary conduct, and motivational support. The lack of implementation of values such as responsibility and respect within the school environment underscores the need to strengthen character education rooted in Islamic values. The study concludes that character education grounded in the Qur’an and Hadith plays a strategic role in producing individuals of integrity who can contribute positively to the nation’s civilization, with the family serving as the first and most influential educational institution.